Agreement between original and Rasch-approved neck disability index - Ze Lu (BMC Medical Research Methodology, 2020)
Abstract Background Given the high prevalence of neck pain, the neck disability index (NDI) has been used to evaluate patient status and treatment outcomes. Modified versions were proposed as solutions to measurement deficits in the NDI. However, the original 10-item NDI was scored out of 50 and is still the most frequently administered version. Examining the extent of agreement between traditional and Rasch-based versions using Bland-Altman (B&A) plots will inform our understanding of score differences that might rise from using different versions. Therefore, the objective of current study was to describe the extent of agreement between different versions of NDI. Methods The current study was a secondary data analysis. The study data was compiled from two prospectively collected data sources. We performed a comprehensive literature search to identify Rasch approved NDI within four databases including Embase, Medline, PubMed, and Google Scholar. Alternate forms and scorings were compared to each other and to the standard NDI. We graphed B&A plots and calculated the mean difference and the 95% limits of agreement (LoA; ±1.96 times the standard deviation). Results Two Rasch approved alternative versions (8 vs 5 items) were identified from 303 screened publications. We analyzed data from 201 (43 males and 158 females) patients attending community clinics for neck pain. We found that the mean difference was approximately 10% of the total score between the 10-item and 5-item (− 4.6 points), whereas the 10-item versus 8-item and 8-item versus 5-item had smaller mean differences (− 2.3 points). The B&A plots displayed wider 95% LoA for the agreement between 10-item and 8-item (LoA: − 12.0, 7.4) and 5-item (LoA: − 14.9, 5.8) compared with the LoA for the 8-item and 5-item (LoA: − 7.8, 3.3). Conclusion Two Rasch-based NDI solutions (8 vs 5 items) which differ in number of items and conceptual construction are available to provide interval level scoring. They both provide scores that are substantially different from the ordinal NDI, which does not provide interval level scoring. Smaller differences between the two Rasch solutions exist and may relate to the items included. Due to the size and unpredictable nature of the bias between measures, they should not be used interchangeably.